Affecting Factors Of Stop Open Defecation Free In The Working Area Of West Simeulue Public Health Centre Simeulue Regency - Barliansyah Barliansyah; Ismail Efendy; Darwin Syamsul (Journal of Ageing And Family, 2022)
Background:The community has healthy latrines in the work area of the West Simeulue Community Health Center as many as 1,024 families (64.8%) of the total 1,581 households have not reached the target of 100% so that there are people defecating in the garden, rice fields, house yards, the beach and river. The purpose of this study was to determine the factors that influence open defecation free in the working area of the Health Centre. Method:This type of research is analytic survey with cross sectional study approach. The population was 1,581 families and the sampling technique was purposive sampling. Quantitative data were analyzed univariately, bivariately and multivariately. Results:The results showed knowledge (0.021), attitude (0.017), ownership of healthy latrines (0.036), the role of the head of the family (0.010), and the role of health workers (0.023) influencing the implementation of open defecation. Conclusion: Knowledge, attitude, ownership of healthy latrines, the role of the head of the family, and the role of health workers influence the open defecation. Keywords: Stop, Open Defecation Free, Society